The Provenance of the Radziwill Chronicle - Olena Rusyna (Київські історичні студії)
The Radziwill chronicle is a unique illuminated Cyrillic manuscript of the late 15th century. Its miniatures cover historical period from the mythical beginnings of Rus’ up to the early 13th century. Unfortunately, neither chronicle’s text nor its miniatures shed light on the milieu and place of its creation. This fact causes scholarly interest in the manuscript’s marginalia which were analyzed earlier just in the context of pre-Radziwill stages of its existence. The attempts to study extratexts of the Radziwill chronicle through the prism of its origin are the main object of the paper. It seems to be the issue of great importance to assess the ensuing results and thus the efficiency of this new methodology. Main attention is paid to the works of those authors who assert that the Radziwill chronicle has Volhynian provenance. Since the times of Oleksii Shakhmatov it is generally believed that the Radziwill chronicle was compiled somewhere in the Western Rus’ (in Smolensk or, less likely, Polotsk). This notion is mostly based on the results of the chronicle’s linguistic analysis made by Vsevolod Hantsov. As to the “Volhynian” concept, it originates from a marginal remark with a rather dubious dating. Shakhmatov insisted on the date 1528 while a number of scholars disagree with his opinion proposing 1487 as a date when marginalia emerged. The detailed examination of “Volhynian” theory demonstrated that it has no scholarly value and thus should be completely ignored. In addition to its debunking the paper contains author’s vision of the problem in connection with the political history of Smolensk region on the verge of the 15th–16th centuries.